Digital phenotyping: An equal opportunity approach to reducing disparities in Alzheimer's disease and related dementia research - Gabrielle B. Britton; Li‐Kai Huang; Alcibiades E. Villarreal; Allan Levey; Anthony Philippakis; Chaur‐Jong Hu; Cheng Chang Yang; Declare Mushi; Diana C. Oviedo; Giselle Rangel; Jor Sam Ho; Louisa Thompson; et al. (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring, 2023)
Abstract A rapidly aging world population is fueling a concomitant increase in Alzheimer's disease (AD) and related dementias (ADRD). Scientific inquiry, however, has largely focused on White populations in Australia, the European Union, and North America. As such, there is an incomplete understanding of AD in other populations. In this perspective, we describe research efforts and challenges of cohort studies from three regions of the world: Central America, East Africa, and East Asia. These cohorts are engaging with the Davos Alzheimer's Collaborative (DAC), a global partnership that brings together cohorts from around the world to advance understanding of AD. Each cohort is poised to leverage the widespread use of mobile devices to integrate digital phenotyping into current methodologies and mitigate the lack of representativeness in AD research of racial and ethnic minorities across the globe. In addition to methods that these three cohorts are already using, DAC has developed a digital phenotyping protocol that can collect ADRD‐related data remotely via smartphone and/or in clinic via a tablet to generate a common data elements digital dataset that can be harmonized with additional clinical and molecular data being collected at each cohort site and when combined across cohorts and made accessible can provide a global data resource that is more racially/ethnically represented of the world population.